TR: COP27 – Interview with Youssef – Regional TV - IWMI, Communication Team (International Water Management Institute, 2023)
In his interview with Channel 1 of Egypt’s National TV during the COP27, Dr Youssef Brouziyne, the IWMI’s Regional Representative in the MENA region highlighted the role of Global North community in building trust with the Global South regarding their commitments in the previous COPs. Dr Brouziyne featured the importance of dialogue in this regards and he mentioned the example of the High-Level Roundtable on Water Security, where IWMI was represented by its Director General, that helped to showcase the absolute linkages between climate action and water security within the highest diplomatic representations at COP27. Dr Brouziyne also gave examples on the on-ground implementation and the ongoing collaboration between IWMI and MENA governments, donors and civil society to overcome climate change related challenges.